A Case of Wide-Complex Tachycardia Due to Atrial Tachycardia Diagnosed by Non-Invasive Programmed Stimulation - Sohinki, Daniel; Wiegn, Phi; Obel, Owen A. (Archives of Clinical and Medical Case Reports, 2021)
<gdiv></gdiv>